When HRIS Drives Performance: Revealing the Dual Mediating Power of Job Involvement and Work Centrality - Setyorini, Noni; Nastiti, Prianka; Fathurachman, Chadyan; Suniroh, Siti; Nugroho, Kiki (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
Organizations are increasingly adopting Human Resource Information Systems (HRIS) to enhance HRM effectiveness and strengthen employee performance in digitally driven work environments. This study examines the effects of HRIS on job involvement, work centrality, and employee performance, while also evaluating the dual mediating roles of job involvement and work centrality. Data were collected from 200 employees selected through nonprobability sampling, targeting individuals with direct experience using HRIS. The measurement and structural models were analyzed using SmartPLS 4. The results indicate that HRIS significantly enhances job involvement, work centrality, and employee performance. Job involvement also shows a positive influence on performance, whereas work centrality does not exhibit a significant direct effect. Mediation analysis further reveals that job involvement significantly mediates the relationship between HRIS and employee performance, while work centrality does not. These findings suggest that HRIS improves employee performance primarily by fostering higher involvement rather than by strengthening work centrality. This study contributes to the literature by clarifying the psychological mechanisms through which digital HR systems influence employee outcomes and offers practical implications for organizations seeking to optimize HRIS utilization to enhance workforce performance.